Edukasi Remaja Berkarakter Berbasis IMTAQ dan Kesehatan Jasmani dalam Pencegahan Penyalahgunaan Narkoba - Lamusu, Zulkifli (Universitas Negeri Gorontalo, 2025)
This community service activity aimed to strengthen adolescents’ character by fostering a balance between faith and piety (iman and taqwa) as well as physical and spiritual health as a preventive effort against drug abuse among students of MTs Al-Falah Fi’lial Pulubala, Gorontalo Regency. The program was implemented using an educative–participatory approach through interactive lectures, question-and-answer sessions, group discussions, and role-play simulations. Participants consisted of madrasah students who were actively involved in all stages of the activity. Evaluation was conducted using pre-test and post-test instruments, supported by observations and participant feedback to assess changes in knowledge, attitudes, and engagement. The results showed a significant improvement in students’ understanding of the dangers of drug abuse and the importance of maintaining physical and spiritual well-being. In addition, students demonstrated more positive attitudes, stronger rejection of drug-related behaviors, and increased awareness of character values rooted in religious teachings. Overall, this community service program proved effective in enhancing adolescents’ resilience against drug abuse through an integrated approach combining character education, religiosity, and healthy lifestyle promotion within the school environment.